The search for a common language : environmental writing and education - Graulich, Melody, 1951- (UPCC book collections on Project MUSE., 2005)
A stellar group of writers, scientists, and educators illuminate the intersections between environmental science, creative writing, and education, considering ways to strengthen communication between differing fields with common interests.